Taming social media in higher education classrooms - Freeman, Wendy (Proceedings of the International Conference on Networked Learning, 2014)
Social media such as Twitter and Facebook have become a part of our everyday communication networks. As new communication technologies become integrated into our routine practices, higher education is called upon to accommodate these platforms in order to ensure that students are prepared as skilled digital citizens. Studies of social media use in higher education classrooms are finding that these same technologies that are transforming our socio-technical communication channels outside the boundaries of the classroom are failing to live up to that same potential in educational contexts. Technology domestication describes a process by which individuals or groups encounter and appropriate a new technology into their everyday routines by focusing on the social and political meanings that people ascribe to technology as they use it. This study explores the domestication of social media by university faculty who use these tools for their teaching. This paper reports preliminary findings from interviews with six university instructors who report integrating social media tools into their classroom teaching. Semi-structured interviews were analysed according to the elements of the domestication process proposed by Silverstone (2006). Preliminary findings suggest the following themes as social media is appropriated for teaching in higher education classrooms: (1) faculty use social media alongside other more traditional educational technologies such as learning management systems; (2) appropriation of social media relies on a pre-existing technological infrastructure that includes ubiquitous access to the internet; (3) the incorporation of social media was considered carefully as part of a fundamentally student-centred, participatory orientation to teaching; and, (4) faculty in the study used social media extensively in their personal lives first before bringing it into their classrooms. Domestication theory provides a useful lens for exploring how technologies become tamed through use. This notion of taming suggests that not only are technologies shaped through use, but they also shape action. Through interviews, faculty revealed that although social media technologies had become domesticated in their everyday lives, these same technologies were far from tamed in their educational uses. This paper explores the steps faculty are taking with their students to domesticate social media in their higher education classrooms.